The relationship between environmental factors and the diversity and abundance of flower-visitor insects on chili pepper in dry season - Sururin, Fahma Wardah; Muzakhar, Kahar; Khafiyya, Nida An; Purwatiningsih, Purwatiningsih (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Approximately 80% of flowering plants are highly dependent on insect pollination, including the chili pepper (Capsicum frutescens). Environmental conditions serve as parameters for insects in their activities. Therefore, this study was conducted to determine the diversity and abundance of flower-visiting insects in C. frutescens and their environmental factors. Field observations of flower-visiting insects were conducted during the dry season utilizing aerial capture methods. The data was analyzed using diversity, abundance, evenness, and dominance indices equations. Multiple linear regression analysis was also conducted to determine the abiotic and biotic factors (environmental factors) that influence the abundance of flower-visiting insects. The analysis results showed that a moderate trend in the diversity of insect and as many as 33% of the total recorded insect individuals belong to the Vespidae family. The Allorhynchium argentatum showed the highest species abundance (27% individuals). Based on the multiple regression analysis results, environmental factors had a non-significant native influence on the abundance of flower-visiting insects. Environmental conditions during the dry season have a weak influence on insect interactions with plants.